The Traditional Mongolian Medicine Qiqirigan-8 Effects on Lipid Metabolism and Inflammation in Obesity: Pharmacodynamic Evaluation and Relevant Metabolites - Narenmandula,; Hongmei,; Ding, Xiaoqing; Li, Kexin; Hashentuya,; Yang, Dezhi; Wendurige,; Yang, Rui; Yang, Dandan; Tana,; Wang, Haisheng; Eerdunduleng,; et al. (Frontiers in Pharmacology, 2022)
Objective: Traditional Mongolian Medicine Qiqirigan-8 (MMQ-8) is a Chinese botanical drug with effective pharmacological properties in obesity. However, the pharmacological mechanism of MMQ-8 remains unclear. This study aimed to determine the active metabolites of MMQ-8 and its therapeutic effects on lipid metabolism and inflammation. Methods: The active metabolites of MMQ-8 were identified by ultrahigh-performance liquid chromatograph Q extractive mass spectrometry (UHPLC-QE-MS) assay and network analysis. An obesity rat model induced by high-fat diet was used in the study. Serum levels of lipids and inflammatory factors were detected using biochemical analysis and enzyme-linked immunosorbent assay (ELISA). Pathological analysis of liver tissues and arteries was conducted with hematoxylin & eosin (H&E) staining and immunohistochemistry. Protein expression of the tumor necrosis factor (TNF) signaling pathway was investigated by Western-blot. Simultaneously, bone marrow cells were used for RNA sequencing and relevant results were validated by cell culture and quantitative real-time polymerase chain reaction (RT-qPCR). Results: We identified 69 active metabolites and 551 target genes of MMQ-8. Of these, there are 65 active metabolites and 225 target genes closely related to obesity and inflammation. In vivo, we observed that MMQ-8 had general decreasing effects on body weight, white adipose tissue weight, and serum lipids. MMQ-8 treatment notably decreased the liver function markers and hepatic steatosis, and significantly decreased inflammation. In serum, it notably decreased TNF-α, interleukin (IL)-6, and inducible nitric oxide synthase (INOS), while elevating IL-10 levels. MMQ-8 treatment also significantly inhibited proteins phosphorylation of nuclear factor-kappa B inhibitor alpha (IBα), mitogen-activated protein kinase (P38), extracellular regulated kinase 1/2(Erk1/2), and stress-activated protein kinase/c-Jun N-terminal kinase (SAPK/JNK), and decreased vascular endothelium damage and macrophage infiltration and polarization to M1. These findings coincide with the RNA-sequencing data of bone marrow cells and results of in vitro experiments. Conclusions: We determined the pharmacological actions and relevant metabolites of MMQ-8 in obesity for the first time. Our study revealed MMQ-8 can optimize lipid metabolism and reduce chronic inflammation in obesity. However, more in-depth research is needed, for example, to understand the principle of compound compatibility and the inhibition effects on hepatic steatosis, T cell differentiation, and inflammatory signal transduction.